Lenguaje escrito y competencia escribe diversos tipos de textos en su lengua materna en estudiantes del quinto ciclo de la Institución Educativa N° 60024, San Juan 2024 - Panduro Rengifo, Roney Robinzon (2025)
The purpose of the study was to determine the relationship that exists between written language and the competence to write different types of text in the mother tongue in students of the V cycle of the primary level of the educational institution 60024 San Juan, using a research methodology of type basic, with a non experimental design and a correlational scope; To do this, a checklist and a rubric were applied to a sample of 559 students. In this regard, the results show a strong and direct relationship between both variables, with a Pearson correlation coefficient (rxy=0,942). Regarding the dimensions of written language, the functional (rxy=0,878), linguistic (rxy=0,920) and relational (rxy=0,770) principles are closely related to the students' ability to write different texts in their native language, which It shows that the comprehensive development of the dimensions of written language influences the development of writing skills. From the above, it is concluded that it is important to integrate the dimensions of written language in pedagogical strategies.